LITERATURE REVIEW: SOCIAL MEDIA AS A TOOL FOR INTERVENING IN CLEAN AND HEALTHY LIVING BEHAVIOR IN THE COMMUNITY - Sudibyo, Ratna Afriyanti; Djannah, Sitti Nur; Trisnowati, Heni (Persatuan Dosen Kesehatan Masyarakat, 2025)
This study is to investigate the effects of social media-based interventions on public health behavior, especially with regard to eating patterns, smoking behaviors, and good lifestyles. Strict selection criteria were used to guarantee the relevance and quality of the 375 papers from the Garuda site, therefore gathering research data through a systematic literature evaluation. Five papers from the selection fit the requirements for additional investigation. The study technique addresses the reach, efficacy, and degree of usage of social media-based treatments by means of a methodical review and meta-analysis methodology. Studies reveal that social media is really helpful in raising public health awareness, attitudes, and behavior. While Line is more successful than Instagram in increasing knowledge of the risks of electronic cigarettes, WhatsApp-based counseling greatly enhances clean and healthy living practices. This study helps legislators and social media-based providers of health programs to improve the success of health promotion by offering direction. By means of better social media usage techniques, interventions can reach a larger community and have a more homogeneous effect on enhancing public health.